Nanoparticle uptake by macrophages in vulnerable plaques for atherosclerosis diagnosis. - Melzer, S.; Ankri, R.; Fixler, D.; Tarnok, A. (J Biophotonics, 2015)
The composition of atherosclerotic (AS) plaques is crucial concerning rupture, thrombosis and clinical events. Two plaque types are distinguished: stable and vulnerable plaques. Vulnerable plaques are rich in inflammatory cells, mostly only M1 macrophages, and are highly susceptible to rupture. These plaques represent a high risk particularly with the standard invasive diagnosis by coronary angiography. So far there are no non-invasive low-risk clinical approaches available to detect and distinguish AS plaque types in vivo. The perspective review introduces a whole work-flow for a novel approach for non-invasive detection and classification of AS plaques using the diffusion reflection method with gold nanoparticle loaded macrophages in combination with flow and image cytometric analysis for quality assurance. Classical biophotonic methods for AS diagnosis are summarized. Phenotyping of monocytes and macrophages are discussed for specific subset labelling by nanomaterials, as well as existing studies and first experimental proofs of concept for the novel approach are shown. In vitro and in vivo detection of NP loaded macrophages (MPhi). Different ways of MPhi labelling include (1) in vitro labelling in suspension (whole blood or buffy coat) or (2) labelling of short-term MPhi cultures with re-injection of MPhi-NP into the animal to detect migration of the cells in the plaques and (3) in vivo injection of NP into the organism.
Keywords: Animals; Atherosclerosis/classification/*diagnosis/metabolism; *Contrast Media/chemistry; Diagnostic Imaging/*methods; Gold/chemistry; Humans; Macrophages/*metabolism; *Metal Nanoparticles/chemistry; Plaque, Atherosclerotic/classification/*diagnosis/metabolism